Development of a Highly Effective African Swine Fever Virus Vaccine by Deletion of the I177L Gene Results in Sterile Immunity against the Current Epidemic Eurasia Strain - Borca, Manuel V.; Ramirez-Medina, Elizabeth; Silva, Ediane; Vuono, Elizabeth; Rai, Ayushi; Pruitt, Sarah; Holinka, Lauren G.; Velazquez-Salinas, Lauro; Zhu, James; Gladue, Douglas P. (Journal of virology, 2020)
Currently, there is no commercially available vaccine against African swine fever. Outbreaks of this disease are devastating the swine industry from Central Europe to East Asia, and they are being caused by circulating strains of African swine fever virus derived from the Georgia 2007 isolate. Here, we report the discovery of a previously uncharacterized virus gene, which when deleted completely attenuates the Georgia isolate. Importantly, animals infected with this genetically modified virus were protected from developing ASF after challenge with the virulent parental virus. Interestingly, ASFV-G-ΔI177L confers protection even at low doses (10 2 HAD 50 ) and remains completely attenuated when inoculated at high doses (10 6 HAD 50 ), demonstrating its potential as a safe vaccine candidate. At medium or higher doses (10 4 HAD 50 ), sterile immunity is achieved. Therefore, ASFV-G-ΔI177L is a novel efficacious experimental ASF vaccine protecting pigs from the epidemiologically relevant ASFV Georgia isolate. African swine fever virus (ASFV) is the etiological agent of a contagious and often lethal disease of domestic pigs that has significant economic consequences for the swine industry. The disease is devastating the swine industry in Central Europe and East Asia, with current outbreaks caused by circulating strains of ASFV derived from the 2007 Georgia isolate (ASFV-G), a genotype II ASFV. In the absence of any available vaccines, African swine fever (ASF) outbreak containment relies on the control and culling of infected animals. Limited cross-protection studies suggest that in order to ensure a vaccine is effective, it must be derived from the current outbreak strain or at the very least from an isolate with the same genotype. Here, we report the discovery that the deletion of a previously uncharacterized gene, I177L, from the highly virulent ASFV-G produces complete virus attenuation in swine. Animals inoculated intramuscularly with the virus lacking the I177L gene, ASFV-G-ΔI177L, at a dose range of 10 2 to 10 6 50% hemadsorbing doses (HAD 50 ), remained clinically normal during the 28-day observational period. All ASFV-G-ΔI177L-infected animals had low viremia titers, showed no virus shedding, and developed a strong virus-specific antibody response; importantly, they were protected when challenged with the virulent parental strain ASFV-G. ASFV-G-ΔI177L is one of the few experimental vaccine candidate virus strains reported to be able to induce protection against the ASFV Georgia isolate, and it is the first vaccine capable of inducing sterile immunity against the current ASFV strain responsible for recent outbreaks. IMPORTANCE Currently, there is no commercially available vaccine against African swine fever. Outbreaks of this disease are devastating the swine industry from Central Europe to East Asia, and they are being caused by circulating strains of African swine fever virus derived from the Georgia 2007 isolate. Here, we report the discovery of a previously uncharacterized virus gene, which when deleted completely attenuates the Georgia isolate. Importantly, animals infected with this genetically modified virus were protected from developing ASF after challenge with the virulent parental virus. Interestingly, ASFV-G-ΔI177L confers protection even at low doses (10 2 HAD 50 ) and remains completely attenuated when inoculated at high doses (10 6 HAD 50 ), demonstrating its potential as a safe vaccine candidate. At medium or higher doses (10 4 HAD 50 ), sterile immunity is achieved. Therefore, ASFV-G-ΔI177L is a novel efficacious experimental ASF vaccine protecting pigs from the epidemiologically relevant ASFV Georgia isolate.